Study of electronic, magnetic and optical properties of KMS2 (M = Nd, Ho, Er and Lu): first principle calculations. (12th June 2017) - Ahmed, Nisar; Nisar, Jawad; Kouser, R; Nabi, Azeem G; Mukhtar, S; Saeed, Yasir; Nasim, M H
Abstract: Wide band gap magnetic semiconductors made of lanthanide compounds have a wide range of applications in opto-magneto-electronic industry and electro (photo) luminescence devices. We have carried out a systematic study of electronic, magnetic and optical properties of rare earth potassium sulfides KMS2 (M  =  Nd, Ho, Er, and Lu) using density functional theory (DFT) with full potential linearized augmented plane wave method (FP-LAPW). Different exchange and correlation approximations are employed such as generalized gradient approximation (GGA), GGA  +   U and TB-mBJ. It is inferred that the GGA  +   U approach correctly predicts the localized behavior of 4 f electrons in lanthanide atoms for the calculation of band gaps, electronic, magnetic and optical properties. All compounds are stable in ferromagnetic phase except KLuS2, while KLuS2 is a non-magnetic semiconductor because there is no unpaired f -electron. Band gaps of KMS2 are estimated and these materials are found to be wide band gap semiconductors. These materials absorb mainly ultraviolet (UV) radiations, which make them good photoluminescent materials with a strong dependence on the direction of the polarization of incident photons.